Colonialism, Computerized: The Canada Land Inventory and the Canada Geographic Information System at Library and Archives Canada - Castron, Melissa M. (Archivaria, 2022)
This article argues for the incorporation of a transdisciplinary approach to cartographic materials in archives, especially in relation to archival description and preservation. Delving into the theoretical foundations and developments in the fields of archival studies and cartography, it explores the creation of cartographic materials and focuses on their processing by archives (i.e., their appraisal, arrangement, description, and preservation and the means of making them available to archival researchers). The lag between theoretical developments and practical applications is illustrated through the creation and management of the Canada Land Inventory (CLI) and Canada Geographic Information System (CGIS) materials held by Library and Archives Canada. An analysis of the creation and ongoing management of these materials highlights the role of cartography and archives in the formation of Canada as a modern colonial state and in the ongoing dispossession of Indigenous Peoples.